2012
DOI: 10.1021/ja210687r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Transistor and Solar Cell Applications of a Naphthobisthiadiazole-Based Semiconducting Polymer

Abstract: We report the synthesis and characterization of a novel donor-acceptor semiconducting polymer bearing naphthobisthiadiazole (NTz), a doubly benzothiadiazole (BTz)-fused ring, and its applications to organic field-effect transistors and bulk heterojunction solar cells. With NTz's highly π-extended structure and strong electron affinity, the NTz-based polymer (PNTz4T) affords a smaller bandgap and a deeper HOMO level than the BTz-based polymer (PBTz4T). PNTz4T exhibits not only high field-effect mobilities of ~0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
243
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(252 citation statements)
references
References 60 publications
7
243
2
Order By: Relevance
“…Liu et al reported analogous copolymer of quarterthiophene and fBT with 10.8% PCE by controlling morphology and crystallinity [8]. Polymer orientation and its gradient in the depth direction are important for improving hole transport and consequent device performance [9,10]. As such, Vohra et al have reported quarterthiophene and naphthothiadiazole (NTz) copolymer achieving 10.1% PCE [11].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported analogous copolymer of quarterthiophene and fBT with 10.8% PCE by controlling morphology and crystallinity [8]. Polymer orientation and its gradient in the depth direction are important for improving hole transport and consequent device performance [9,10]. As such, Vohra et al have reported quarterthiophene and naphthothiadiazole (NTz) copolymer achieving 10.1% PCE [11].…”
Section: Introductionmentioning
confidence: 99%
“…Intensive interdisciplinary efforts have been dedicated to improving the power conversion efficiencies (PCEs) of solution-processed polymer bulk heterojunction (BHJ) solar cells [4][5][6][7][8][9][10]. More recently, BHJ OSCs using solution-processed small molecules as donors have also attracted increasing attentions [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, covalently fastening adjacent aromatic units, the polymer could have enhanced effective p-conjugation, lower bandgap, and strong light-harvesting, which induce p-p stacking and facilitate the charge transport by intermolecular hopping [23][24][25][26]. Therefore, fused-ring building blocks are widely used in synthesis of conjugated polymers, such as naphtho [2,3-b:6,7-d 0 ]dithiophene (NDT) [27], thienyl-phenylene-thienylene-phenylene-thienyl (TPTPT) [28], indaceno dithiophene (IDTT) [29], naphtho-[1,2-c:5,6-c]bis [1,2,5]-thiadiazole (NT) [30,31]. Cheng et al reported a multifused DTPBT unit (Scheme 1) [32], which was prepared by covalently fastening adjacent electron-rich donor (thieno [3,2-b]pyrrole) and electron-deficient acceptor (BT).…”
Section: Introductionmentioning
confidence: 99%